DIMENSION OF UNILATERAL SHAPING OF THE CONTENT OF THE NOMINATIVE EMPLOYMENT RELATIONSHIP - Rogozińska-Mitrut, J. (Wydawnictwo Naukowe IVG, 2021)
The notion of nominative employment relationship indicated in the title refers mainly to employment relationships by appointment in the public sector with a special employee-service legal status determined by professional pragmatics, with an expanded catalog of duties and a strengthened system of responsibility, as well as special rights not present on the grounds of general employment law.
Keywords: employment relationship; legal actions; disciplinary punishment